Evaluating stress and it associated factors in mothers of preterm infants in NICU: a cross-sectional study - Pavlyshyn, Halyna; Sarapuk, Iryna (Frontiers in Global Women's Health, 2025)
IntroductionProviding care of preterm infants in the NICU is a significant source of psychological and emotional stress for both infants and parents. The purpose of the study was to investigate the relationship between gestational age (GA) and maternal stress levels in the neonatal intensive care unit (NICU) setting and to identify additional demographic and clinical factors that may contribute to or exacerbate maternal stress during the infant's NICU hospitalization.Materials and methodsThis observational, cross-sectional prospective study included 247 mothers of preterm infants. Maternal stress and worry were assessed using the PSS: NICU questionnaires. PSS: NICU items were organized into three subscales: Sights and Sounds (S1), Infant Appearance and Behavior (S2), and Parental Role Alteration (S3).ResultsModerate/high NICU-related stress among mothers of preterm infants was more common when infants were born before 32 weeks (p = 0.031), in cases of neonatal seizures (p = 0.027), sepsis (p = 0.032), and invasive ventilation (p = 0.027). Logistic regression showed that gestational age under 32 weeks and neonatal seizures significantly increased the risk of moderate/high maternal stress (OR = 2.90, 95% CI: 1.26–6.68, p = 0.012; OR = 9.83, 95% CI: 1.19–80.80, p = 0.033, respectively).ConclusionNICU-related stress among mothers of preterm infants significantly associated with gestational age below 32 weeks and exacerbated by neonatal seizures. These factors can help identify mothers at high risk who may need focused support in the NICU, considering both the infant's condition and the mother's psychological well-being.